Transplantation of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells Improves Cartilage Repair in a Rabbit Model - Yang, Guihua (Biomed Res Int, 2021)
The aim of this study was to investigate the therapeutic efficacy and safety of transplanting human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) in the treatment of cartilage injury. First, the articular cartilage defect model in rabbits was constructed. Then, the identified hUCB-MSCs and rabbit bone marrow stem cells (rBM-MSCs) were transplanted into the bone defect, respectively, and the cartilage repair effect was observed by hematoxylin-eosin (HE) staining and immunohistochemistry. Besides, the glycosaminoglycan (GAG) content and biomechanics of the restoration area were also evaluated. In our study, hUCB-MSCs and rBM-MSCs exhibited typical MSC characteristics, with positive expressions of CD73, CD105, and CD90 and negative for CD45, CD34, CD14, and HLA-DR. After the transplantation of hUCB-MSCs and rBM-MSCs, the overall quality of cartilage tissue was significantly improved, and the recipients did not show significant side effects in general. However, the expression of matrix metalloproteinase-13 (MMP-13) in the de novo tissues of the hUCB-MSCs and rBM-MSCs groups was both increased, indicating that the novel tissues may have some potential osteoarthritic changes. In conclusion, our results suggest the therapeutic effect of hUCB-MSCs transplantation in cartilage regeneration, providing a promising future in the clinical treatment of cartilage injury.